2018
DOI: 10.1016/j.physleta.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A graph with fractional revival

Abstract: An example of a graph that admits balanced fractional revival between antipodes is presented. It is obtained by establishing the correspondence between the quantum walk on a hypercube where the opposite vertices across the diagonals of each face are connected and, the coherent transport of single excitations in the extension of the Krawtchouk spin chain with next-to-nearest neighbour interactions.Comment: 16 page

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…where the last line follows from (2). Since this sum is even, it is not ±1, and thus we get pretty good fractional revival by Theorem 2.4.…”
Section: Ada Chan Whitney Drazen or Eisenberg Mark Kempton And Gabor Lippnermentioning
confidence: 80%
See 1 more Smart Citation
“…where the last line follows from (2). Since this sum is even, it is not ±1, and thus we get pretty good fractional revival by Theorem 2.4.…”
Section: Ada Chan Whitney Drazen or Eisenberg Mark Kempton And Gabor Lippnermentioning
confidence: 80%
“…Fractional revival is important in the study of entanglement generation [6]. Fractional revival in weighted paths is studied in [2,6,7,9,13,14]. In simple, unweighted paths, it has been shown that fractional revival can occur between two nodes only in paths of length 2, 3, or 4 [6].…”
Section: Introductionmentioning
confidence: 99%
“…We shall call this graph ordered Hamming graph (of depth 2). Now, following [4,11], we consider the projection of the quantum walk on the ordered Hamming graph G α,β to the "column subspaces" to identify the corresponding spin lattice.…”
Section: Special Weighted Graphs and Their Projectionsmentioning
confidence: 99%
“…Apart from the full revival at t = T and the mirror revival at t = T /2, there is also fractional revival [35,36,38] occurring at times t = (α/β) (T /2), where α and β are coprime integers. As we shall see, the wave function…”
Section: B Fractional Revivalmentioning
confidence: 99%
“…Experimentally, the properties of quantum carpets have been illustrated in a wide class of systems, for example, Rydberg atom [31], optical lat- * songxk@sustc.edu.cn † yung@sustc.edu.cn tice [32], cavity quantum electrodynamic systems [33], optical waveguide [34], and so on. Apart from the full revival of the initial wave function, the time evolution in a quantum carpet also contains solutions cloning initial wave functions throughout the well -a phenomena called "fractional revival" [35][36][37][38]. It originates from the the phase alignment with non-adjacent eigenstates.…”
Section: Introductionmentioning
confidence: 99%